2014
DOI: 10.1103/physrevb.90.195139
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic charge dynamics in the quantum spin-liquid candidateκ(BEDT-TTF)2Cu2(CN)3

Abstract: We have in detail characterized the anisotropic charge response of the dimer Mott insulator κ-(BEDT-TTF)2Cu2(CN)3 by dc conductivity, Hall effect and dielectric spectroscopy. At room temperature the Hall coefficient is positive and close to the value expected from stoichiometry; the temperature behavior follows the dc resistivity ρ(T ). Within the planes the dc conductivity is well described by variable-range hopping in two dimensions; this model, however, fails for the out-ofplane direction. An unusually broa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
108
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(126 citation statements)
references
References 62 publications
18
108
0
Order By: Relevance
“…The κ-CN system displays insulating behavior over the wide temperaturerange measured. Our dc resistivity data together with Hall coefficient and magnetoresistance data suggest that the charge transport takes place via 2D variable-range hopping among localized states [38,39]. We note that Kawamoto and collaborators pointed out previously the presence of the charge inhomogeneity based on their NMR and dc data on κ-CN [40].…”
Section: (Tmttf) 2 X and α-(Bedt-ttf) 2 Imentioning
confidence: 61%
See 1 more Smart Citation
“…The κ-CN system displays insulating behavior over the wide temperaturerange measured. Our dc resistivity data together with Hall coefficient and magnetoresistance data suggest that the charge transport takes place via 2D variable-range hopping among localized states [38,39]. We note that Kawamoto and collaborators pointed out previously the presence of the charge inhomogeneity based on their NMR and dc data on κ-CN [40].…”
Section: (Tmttf) 2 X and α-(Bedt-ttf) 2 Imentioning
confidence: 61%
“…Lack of spectroscopic evidence for the static electric dipoles on the dimers made it clear that further experimental efforts were needed in order to better understand the origin of the dielectric and charge response in this system. Our dielectric spectroscopy data for ac electric fields along the in-plane c-axis showed the presence of one dielectric mode described well by a Cole-Cole function [38]. The dielectric strength ε Δ and the mean relaxation time τ 0 for asingle crystal of κ-CN are shown in Fig.…”
Section: (Tmttf) 2 X and α-(Bedt-ttf) 2 Imentioning
confidence: 98%
“…In addition, it has been suggested that the cation-anion interaction plays an important role in realizing the QSL state in the κ-type ET salts [29][30][31]. Therefore, we discuss the cation-anion interaction in the β -Pd(dmit) 2 salts, especially the S· · · H-C short contacts between the terminal thioketone group of the Pd(dmit) 2 molecule and the hydrogen atom in the cation.…”
Section: Cation-anion Interactionsmentioning
confidence: 97%
“…These findings support our interpretation that the relaxor-like dielectric behavior in the kHz-MHz range resembles the dynamics due to charge defects in the random-domain structure of κ-CuCN. 12 In order to elucidate the ferroelectric nature of QSL and advance the understanding of its dielectric response, the newly synthetized Mott dimer insulator κ-(BEDT-TTF) 2 Ag 2 (CN) 3 , 23 called κ-AgCN, has drawn our attention as recent NMR experiments have indicated a QSL ground state. 24 In this compound (Fig.…”
mentioning
confidence: 99%
“…The behavior demonstrates a ferroelectric-like response in the presence of disorder, similar to the observations in κ-CuCN. 8,12 In order to understand the observed dielectric and vibrational features, we have carried out ab-initio calculations in the framework of density functional theory (DFT) as implemented in the VASP code using the projector augmented-wave method; the phonon modes were obtained with PHONOPY code via the DFTderived force constants. [28][29][30][31][32] Our numerical calculations are based on the x-ray data taken at 150 K, solved in P2 1 /c and reduced to P1.…”
mentioning
confidence: 99%